Stabilization of Black Phosphorus by Sonication‐Assisted Simultaneous Exfoliation and Functionalization. Issue 72 (23rd November 2020) - van Druenen, Maart; Collins, Timothy; Davitt, Fionán; Doherty, Jessica; Collins, Gillian; Sofer, Zdeněk; Holmes, Justin D.
Abstract: Black phosphorus (BP) has extraordinary properties, but its ambient instability remains a critical challenge. Functionalization has been employed to overcome the sensitivity of BP to ambient conditions while preserving its properties. Herein, a simultaneous exfoliation–functionalization process is reported that functionalizes BP flakes during exfoliation and thus provides increased protection, which can be attributed to minimal exposure of the flakes to ambient oxygen and water. A tetrabutylammonium salt was employed for intercalation of BP, resulting in the formation of flakes with large lateral dimensions. The addition of an aryl iodide or an aryl iodonium salt to the exfoliation solvent creates a scalable strategy for the production of functionalized few‐layer BP flakes. The ambient stability of functionalized BP was prolonged to a period of one week, as revealed by STEM, AFM, and X‐ray photoelectron spectroscopy. Abstract : Flaky but stable : Black phosphorus (BP) was simultaneously exfoliated with a tetrabutylammonium salt and functionalized with an aryl iodide to produce few‐layer BP flakes with large lateral dimensions and enhanced ambient stability for up to one week. Simultaneous exfoliation–functionalization ensures immediate functionalization, which greatly restricts the oxidation of BP, while solvent passivation is minimized by functionalization.